Ventilation performance assessment of an educational building in a hot and humid climate - Ali, Maisarah; Oladokun, Majeed; Osman, Samsul Bahrin; Samsuddin, Niza; Hamzah, Hairul Aini; Salleh, Md. Noor (Springer, 2015)
Air Handling Units in mechanical ventilation system possess a high degree of potential to circulate contaminants within occupied spaces of a building which often results in sick building syndrome (SBS), building related illness (BRI) and other indoor air quality (IAQ) related issues. This happens despite the expected role of ventilation systems to create a balance of thermal comfort and indoor air quality to the building occupants as well as the stored components. In the hot and humid climate mechanical ventilation systems play an important role of controlling the indoor hygrothermal conditions. Inadequate performance of the mechanical ventilation systems result in several issues ranging from human occupants discomfort, mechanical damages to archival materials and mould problem amongst others. This study presents the measurement and analysis of the mechanical ventilation systems’ performance and its effect on various indoor spaces in an academic building in Malaysia. Measurement of airflow, thermal and hygric conditions of the facility together with the aero-biological sampling were executed. The ventilation performance assessment revealed that the AHU fails in its cooling and dehumidification capacities as most of the occupied zones witnessed elevated humidity and low temperature and hence poor hygrothermal performance. On the other hand, results of bio-aerosol assessment indicates that the AHU performs well in its decontamination capacities by reducing the microbial level between the AHU and the occupied zones. The dominant species of mould in the assessed spaces are Penicillium sp., Yeast, Cladosporium sp., and Chaetomium sp. with 100% occurrence in all the assessed space. On the other hand, Black Mold, Syntalidium sp., and zygomycetes are the least species in spaces with 25% occurrence. The presence of black mould portends a great danger to the occupants’ health and therefore requires urgent attention. Keywords—Ventilation performance, bio-aerosol Assessment, Indoor Air Quality, Building Related Illness, Hygrothermal Performance, Cooling and Dehumidification.